Changing the workplace safety culture - McKinnon, Ron C. (Boca Raton : CRC Press/Taylor & Francis, 2014)
'The only way to ensure that accidents and their consequences are tackled at the source is to identify and eliminate the workplace risks before, rather than after the event. The ongoing identification of workplace and worker risk must become a value to an organization and must occur automatically, as part of the culture of the organization if accidental losses are to be eliminated. This book shows that an organization's safety culture is the driving force behind successful safety management systems that constantly identify and reduce risk thus eliminating accidents which lead to injuries, property damage or environmental disasters'--
'Preface Little if any significant progress has been made in the reduction of accidental deaths and injuries at the majority of workplaces. This is despite the fact that workplaces have implemented and followed safety innovations and new approaches. Many of these have proved to be ineffective in preventing injuries, fatal accidents, and other loss-producing events. Some of these safety approaches and innovations are not tried and tested interventions, but are based on the whim of some safety organizations and psychology departments using outdated and inaccurate safety research. These approaches have launched a trend in the safety industry that is followed almost blindly. No one seems to question their validity or effectiveness. Reviewers of this book's proposal felt that 60% or more of the contents should refer to behavior-based safety methodology. I did not understand why until I realized that these reviewers had been taught that workplace safety culture was created, modified, or changed by the behavior of the workers. I agree that behavior has a role in safety culture, but I firmly believe that the state of the workplace, the safety management system, the leadership, and the organization is what changes behavior in the first place. Employees behave according to the expectations of the organization they work for. This book demonstrates how changing the way an organization views and practices safety will impact on the behavior of all employees, including executive and line managers. This is not a book about behavior-based safety, but a guideline on how to establish a long-lasting integrated safety culture into an organization. It is about changing the safety personality at workplaces'--
Includes bibliographical references (pages 211-213) and index.
Keywords: Industrial safety; Work environment